Run-time management of many-core SoCs: A communication-centric approach - Fattah, Mohammad (fi=Turun yliopisto|en=University of Turku|, 2021)
The single core performance hit the power and complexity limits in the beginning of this century, moving the industry towards the design of multi- and many-core system-on-chips (SoCs). The on-chip communication between the cores plays a criticalrole in the performance of these SoCs, with power dissipation, communication latency, scalability to many cores, and reliability against the transistor failures as the main design challenges. Accordingly, we dedicate this thesis to the communicationcentered management of the many-core SoCs, with the goal to advance the state-ofthe-art in addressing these challenges. To this end, we contribute to on-chip communication of many-core SoCs in three main directions. First, we start with a synthesizable SoC with full system simulation. We demonstrate the importance of the networking overhead in a practical system, and propose our sophisticated network interface (NI) that offloads the work from SW to HW. Our results show around 5x and up to 50x higher network performance, compared to previous works. As the second direction of this thesis, we study the significance of run-time application mapping. We demonstrate that contiguous application mapping not only improves the network latency (by 23%) and power dissipation (by 50%), but also improves the system throughput (by 3%) and quality-of-service (QoS) of soft real-time applications (up to 100x less deadline misses). Also our hierarchical run-time application mapping provides 99.41% successful mapping when up to 8 links are broken. As the final direction of the thesis, we propose a fault-tolerant routing algorithm, the maze-routing. It is the first-in-class algorithm that provides guaranteed delivery, a fully-distributed solution, low area overhead (by 16x), and instantaneous reconfiguration (vs. 40K cycles down time of previous works), all at the same time. Besides the individual goals of each contribution, when applicable, we ensure that our solutions scale to extreme network sizes like 12x12 and 16x16. This thesis concludes that the communication overhead and its optimization play a significant role in the performance of many-core SoCs